Inulin Gembili Bulbs (Dioscoreaesculenta) application At Sweet Bread Products to Increase Fiber, Physical Properties and level of acceptance - Arintina Rahayuni; Cahyo Hunandar; Yuwono Setiadi (Poltekkes Kemenkes Semarang, 2014)
This research we increase the amount of fiber in sweet bread and reducing fat, but still tasty, soft. The fiber material used is inulin extracted from gembili tubers which has the similar as fat (mouthfeel). The study was conducted in two stages, introduction stage to obtain formulations of fiber increase and fat reduction, and main research which was divided into 5 level of fat replacement with inulin and 1 control treatment without it. The analysis technique is one way ANOVA at á 1%, advanced test are decided based on variability coefficient. The results shows that the fiber content increased according to the increasing number of fat that are replaced with fiber inulin. It is a significant difference compared to the control treatment by replacing fat with the lowest dose of inulin (M1, 20% fat was replaced by 5 g of inulin). The best level of expansion and tenderness of bread is in the M3 treatment (60% fat replaced by 15 g inulin). The acceptance test can be concluded that replacing fat with inulin does not affect the taste and flavor it is affect the texture and color.